The architecture of the millenary peoples of the altiplano: a female and male configuration, Jaqui Andean (REVISTA NODO, 2019)
The ancestral villages located on the Bolivian highland make an evidence of the wealth of earthen architectural culture existing in the region. The housing system, part of the local architectural heritage, has pitifully been ignored and forgotten, because of the hegemony of the capitalist commercial logic, contributed by the development and progressivism. Today we see this housing system collapsing as time passes by, regardless of its cognitive, historical and cultural content. Within this system, there is evidence of the parity of the muruqu-taru uta (house of circular and quadrangular shape), as the main and specific components of the housing system of the Ayllu and Marka studied on the Highlands. During fieldwork, three spaces were found in the housing system: a) the manqha uta (private home space); b) the taypi uta (central home space); c) uta anqa (environment and contour of the home), where the material-spiritual logic of the Aymara culture is embodied in counterpart, equity and harmonious cosmo-coexistence, presenting a high ecological and environmental knowledge, using natural local materials, thinking about the welfare of the other worlds of cosmos.
Keywords: Muruqu-Taru uta; heritage; earthen construction; house system